Integrasi Hukum Islam dalam Sistem Hukum Nasional melalui Kajian Peradilan Agama Indonesia - Darian Ezra ‘Aabidah; Luhung Cahya Adi; Jezkhiel Septryan Jubilate Oppusunggu; Muhammad Faisal Firdaus; Ahmad Haikal Manggabarani; Baidhowi (CV. ITTC INDONESIA, 2025)
This study aims to critically examine the integration of Islamic law within the Indonesian national legal system, specifically through the role and jurisdiction of the Religious Courts (Peradilan Agama) and the utilization of the Compilation of Islamic Law (KHI) as a primary reference. Although Islamic law is formally recognized, and the KHI is widely employed by judges to resolve marriage, inheritance, and waqf (endowment) cases, this research is driven by two main issues: first, the ongoing debate regarding the binding power of the KHI, which is legally based only on a Presidential Instruction; and second, the overlapping jurisdiction between the Religious Courts and the General Courts (Peradilan Umum) in practice. Operating within the framework of the Pancasila legal state, this research analyzes the consistency of these regulations with the principles of legal certainty, usefulness, and justice. The findings are expected to formulate recommendations for legal reform to strengthen the integration of Islamic law and resolve confusion at the practical level.